2013
DOI: 10.1017/jfm.2013.81
|View full text |Cite
|
Sign up to set email alerts
|

An explicit algebraic model for the subgrid-scale passive scalar flux

Abstract: An explicit algebraic model for the subgrid-scale passive scalar flux.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 60 publications
0
19
0
Order By: Relevance
“…In this region, no viscous convective subrange occurs, and mixing spectra resemble flow spectra as they appear in turbulent jets of subcritical gases. Such a finding suggests that tensorial heat diffusivity models (e.g., [47][48][49][50]) might be appropriate for supercritical flows, in particular for fluids with strong liquid-like character.…”
Section: Thermal Transportmentioning
confidence: 97%
“…In this region, no viscous convective subrange occurs, and mixing spectra resemble flow spectra as they appear in turbulent jets of subcritical gases. Such a finding suggests that tensorial heat diffusivity models (e.g., [47][48][49][50]) might be appropriate for supercritical flows, in particular for fluids with strong liquid-like character.…”
Section: Thermal Transportmentioning
confidence: 97%
“…Performance of the SGS scalar flux model depends on the SGS stress model 3,6 , since the scalar field depend on the predicted velocity field. This is also true for the EASFM which directly includes the SGS stresses in its formulation, see equation (12).…”
Section: B Mean and Rms Of Scalar And Scalar Fluxesmentioning
confidence: 99%
“…Performance of the EASM, a nonlinear mixed model, has been demonstrated for the case of turbulent channel flow at various Reynolds numbers and grid resolutions, channel flow with system rotation in different directions and channel flow with periodic constrictions [1][2][3][4] . These studies illustrate the importance of the nonlinear SGS stress term in the EASM and showed that the assumption of an isotropic linear relationship between the SGS stress and resolved strain-rate tensor, as in the eddy-viscosity models, is not valid in wall-bounded turbulent flows where the SGS anisotropy is appreciable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the previous work, this model has been thoroughly tested in canonical test cases such as homogeneous shear flow and turbulent channel flow, both with stable stratification. It should be noted that similar approaches have been used in LES in both the atmospheric and engineering communities (Findikakis and Street 1979;Wyngaard 2004;Rasam et al 2013Rasam et al , 2014Enriquez and Street 2014).…”
Section: Introductionmentioning
confidence: 99%